A kind of graphite felt with adjustable hardness and softness for vanadium battery and preparation method thereof
By introducing a p -@MOF (POM@MOF) and using carbon nanotubes and high -temperature cross -linking agents on the graphite felt, to prepare a hard and hard -to -adjust graphite felt, solve the problem of low graphite felt activity and large contact resistance. , Improve the energy efficiency and capacity maintenance rate of the battery.
Patent Information
- Application Number
- CN202411400073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing vanadium battery electrode material has low activity, resulting in low energy efficiency, and the contact resistance between the electrode and the plate is large, affecting battery performance.
By introducing a p -@MOF (POM@MOF) on the graphite felt, and enhanced the surface area and surface activity point through organic boron modification and water thermal reactions, combined with carbon nanotubes and high -temperature cross -linking agents to prepare soft and hardcore Utilized graphite felt.
Improve the reaction activity and conductivity of graphite felt, reduce the contact resistance between the electrode and the pole plate, and enhance the energy efficiency and capacity maintenance rate of the battery.
Smart Images

Figure CN118919744B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of vanadium battery electrodes, in particular to a graphite felt with adjustable hardness and softness for vanadium batteries and a preparation method thereof. Background Art
[0002] In recent years, all-vanadium liquid flow batteries (vanadium batteries) have become the focus of new energy storage batteries. They have the advantages of independent capacity, high power, long life, deep discharge and no emission pollution. They can be used as supporting energy storage devices in the power generation process of renewable energy such as wind power and solar energy, and can also achieve frequency and peak regulation in the power grid system. They are suitable for electrochemical energy storage devices for large-scale energy storage.
[0003] At present, the electrode materials with the best electrical properties used in vanadium batteries are porous carbon three-dimensional electrode materials such as graphite felt or carbon felt, which are woven from carbon fibers, have good mechanical strength, and the real specific surface area is much larger than the geometric surface area, which can provide a large electrochemical reaction area. Coupled with good chemical stability and conductivity, it has become one of the research hotspots of vanadium battery electrode materials. However, graphite felt also has some shortcomings, especially the low energy efficiency caused by the low activity of the electrode material and the high contact resistance between the electrode and the plate. In order to solve this problem, scientists have been seeking ways to improve the energy efficiency of batteries and design a simple and high-performance electrode. In addition, the use of high-performance electrode materials and improved electrode structure are one of the effective ways to reduce the investment cost of vanadium batteries. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a graphite felt with adjustable hardness and softness for vanadium battery and a preparation method thereof.
[0005] A method for preparing graphite felt with adjustable hardness and softness for vanadium batteries comprises the following steps:
[0006] Step S1: using organic boron to react H7[P2Mo 17 VO 62 ] were covalently modified to obtain organoboron-modified polyacid nanocapsule molecules (POM);
[0007] Step S2, loading POM into the pores of a metal organic framework (MOF) material through a hydrothermal reaction to obtain POM@MOF;
[0008] Step S3, adding POM@MOF, carbon nanotubes, dispersant, surfactant, stabilizer and high-temperature crosslinking agent into deionized water, dispersing them evenly, and adjusting the proportion of carbon nanotubes to obtain modified A carbon slurry and modified B carbon slurry;
[0009] Step S4, immersing one side of the graphite felt in the modified A carbon slurry and the other side in the modified B carbon slurry, drying in an oven after immersion, and then sintering at high temperature to obtain graphite felt with adjustable hardness and softness.
[0010] Preferably, the covalent modification method in step S1 is to modify H7[P2Mo 17 VO 62 ] and sodium bisulfate are dissolved in deionized water at 80°C, and then organic boron is added. The pH value is adjusted to 1-3 with hydrochloric acid. The reaction time is 20-60 minutes, and POM is obtained by cooling and filtering.
[0011] Preferably, the organic boron in step S1 is selected from dimethylamine borane, morpholine borane and 2-methylpyridine borane.
[0012] Preferably, in step S1, H7[P2Mo 17 VO 62 ]: Organic boron: deionized water = (10~20): 1:1000, H7[P2Mo 17 VO 62 ] and sodium bisulfate is 4:1.
[0013] Preferably, the hydrothermal reaction method in step S2 is: uniformly disperse POM, MOF material and NN dimethylformamide to obtain a mixed solution, add the mixed solution into a reactor, react at 120-200°C for 20-60 hours, cool to room temperature and centrifuge, and vacuum dry the precipitate at 60-80°C for 8-24 hours to obtain POM@MOF.
[0014] Preferably, in step S2, the MOF material is Cu-MOF, Mn-MOF, Ni-MOF, the concentrations of POM and MOF material are 1-3 g / L and 3-15 g / L respectively, and the concentration ratio of POM:MOF material is 1:1-1:5.
[0015] Preferably, in step S3, the dispersant is polyvinyl alcohol, the surfactant is sodium dodecylbenzene sulfonate, the stabilizer is one of nano-alumina and nano-silicon dioxide, and the high-temperature cross-linking agent is one of polyvinyl pyrrolidone K15, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60, polyvinyl pyrrolidone K90, and polyvinyl pyrrolidone K150.
[0016] Preferably, in step S3, the distribution ratio of each group of modified A slurry is 2: (5-10): 0.5: 0.5: 1: 1: 100 for POM@MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water; and the distribution ratio of each group of modified B slurry is 2: (1-5): 0.5: 0.5: 1: 1: 100 for POM@MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water.
[0017] Preferably, the impregnation method in step S4 is: the graphite felt is impregnated with modified carbon slurry A with a thickness of 1 / 2 of the thickness of the graphite felt, the impregnation with modified carbon slurry B with a thickness of 1 / 2 of the thickness of the graphite felt, the graphite felt is dried at a temperature of 80-120°C, and the drying time is 2-5h. The graphite felt high-temperature sintering process is: heating at a heating rate of 5-10°C / min to 250-350°C and keeping warm for 2-4h.
[0018] A graphite felt with adjustable hardness for vanadium battery is prepared by using the above-mentioned graphite felt with adjustable hardness for vanadium battery and its preparation method. In the vanadium battery stack, the harder side of the graphite felt contacts the plate, and the softer side of the graphite felt contacts the diaphragm.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention introduces a polyacid-based metal organic framework (POM@MOF) on the graphite felt. Since POM@MOF has a rich topological structure and high active sites after high-temperature calcination, and has a large specific surface area, the reaction activity of the graphite felt can be improved, thereby improving the battery performance.
[0021] 2. The present invention uses organic boron to treat H7[P2Mo 17 VO 62 ] are covalently modified and loaded into the MOF pores, combining the porosity of the MOF material with the high reactivity of the polyacid, which can increase the specific surface area and surface active points of the polyacid, thereby improving the reactivity of the graphite felt.
[0022] 3. The present invention adds a high-temperature cross-linking agent to the carbon slurry, realizes cross-linking during the sintering process, firmly locks the POM@MOF on the graphite felt, resists electrolyte erosion, improves the stability of the electrode material, and further improves the capacity retention rate.
[0023] 4. The present invention controls the carbon nanotube content in the carbon slurry impregnated on both sides of the graphite felt to adjust the hardness of both sides of the graphite felt, with the plate side being the harder side and the membrane side being the softer side, thereby reducing the contact resistance between the graphite felt and the plate without causing physical damage to the ion membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1The present invention is a schematic flow chart of a method for preparing graphite felt with adjustable hardness and softness for vanadium batteries. DETAILED DESCRIPTION
[0025] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] See also Figure 1 A method for preparing graphite felt with adjustable hardness and softness for vanadium batteries comprises the following steps:
[0027] Step S1: H7[P2Mo 17 VO 62 ] and sodium bisulfate are dissolved in 80°C deionized water, and then an organic boron is added, and the pH value is adjusted to 1-3 with hydrochloric acid. The reaction time is 20-60 minutes, and POM is obtained by cooling and filtering. The organic boron is selected from dimethylamine borane, morpholine borane, and 2-methylpyridine borane; H7[P2Mo 17 VO 62 ], the mass ratio of organic boron and deionized water is (10~20): 1:1000, H7[P2Mo 17 VO 62 The mass ratio of sodium bisulfate to sodium bisulfate is 4:1;
[0028] Step S2: POM and MOF materials are added to a reactor, N-N dimethylformamide is added, the hydrothermal reaction temperature is 120-200°C, the reaction time is 20-60h, the mixture is cooled to room temperature and then centrifuged, and vacuum dried at 60-80°C for 8-24h to obtain POM@MOF; the MOF materials are Cu-MOF, Mn-MOF, and Ni-MOF, the concentrations of POM and MOF materials in the mixed solution are 1-3g / L and 3-15g / L, respectively, and the concentration ratio of POM:MOF materials is 1:1-1:5;
[0029] Step S3: POM@MOF, carbon nanotubes, dispersant, surfactant, stabilizer and high-temperature crosslinking agent are added to deionized water, dispersed evenly, and the ratio of carbon nanotubes is adjusted to obtain modified A carbon slurry and modified B carbon slurry; the dispersant is polyvinyl alcohol, the surfactant is sodium dodecylbenzene sulfonate, the stabilizer is one of nano-alumina and nano-silicon dioxide, and the high-temperature crosslinking agent is polyvinyl pyrrolidone K15, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60, polyvinyl pyrrolidone K90, one of polyvinyl pyrrolidone K150; the distribution ratio of each group of modified A slurry is POM@MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water is 2: (5-10): 0.5: 0.5: 1: 1: 100; the distribution ratio of each group of modified B slurry is POM@MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water is 2: (1-5): 0.5: 0.5: 1: 1: 100;
[0030] Step S4: impregnate one side of the graphite felt in modified carbon slurry A and the other side in modified carbon slurry B, dry in an oven after impregnation, and then perform high-temperature sintering to obtain graphite felt with adjustable hardness and softness; the impregnation method is: the graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt, the drying temperature of the graphite felt is 80-120°C, and the drying time is 2-5h. The high-temperature sintering process of the graphite felt is as follows: the temperature is increased to 250-350°C at a heating rate of 5-10°C / min, and kept warm for 2-4h.
[0031] Embodiment 1: A method for preparing a graphite felt with adjustable hardness for a vanadium battery, comprising the following steps:
[0032] Step S1: 10gH7[P2Mo 17 VO 62 ] and 2.5g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g dimethylamine borane was added, and the pH value was adjusted to 1 with hydrochloric acid. The reaction time was 30min, and the polyacid nanocapsule-like molecules POM modified with dimethylamine borane were obtained by cooling and filtering;
[0033] Step S2: 1 g of dimethylamine borane-modified polyacid nanocapsule molecule POM and 3 g of Cu-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 120°C and the reaction time was 60 h. After cooling to room temperature, the reaction was centrifuged and vacuum dried to obtain POM@MOF. The vacuum drying temperature was 60°C and the time was 24 h.
[0034] Step S3: adding 2gPOM@MOF, 5gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K15 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 1gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K15 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0035] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 80°C for 5 hours. The graphite felt high-temperature sintering process: the temperature is increased to 250°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain graphite felt with adjustable hardness and softness.
[0036] Embodiment 2: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0037] Step S1: 15gH7[P2Mo 17 VO 62 ] and 3.75g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g dimethylamine borane was added, and the pH value was adjusted to 2 with hydrochloric acid. The reaction time was 40min, and the polyacid nanocapsule-like molecules POM modified with dimethylamine borane were obtained by cooling and filtering;
[0038] Step S2: 3 g of dimethylamine borane-modified polyacid nanocapsule molecules POM and 6 g of Cu-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 140 ° C, the reaction time was 50 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 70 ° C for 20 h.
[0039] Step S3: adding 2gPOM@MOF, 6gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K30 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 2gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K30 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0040] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 90°C for 4 hours. The graphite felt high-temperature sintering process: the temperature is increased to 280°C at a heating rate of 10°C / min and kept warm for 3.5 hours to obtain graphite felt with adjustable hardness and softness.
[0041] Embodiment 3: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0042] Step S1: 12gH7[P2Mo 17 VO 62 ] and 3g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g dimethylamine borane was added, and the pH value was adjusted to 3 with hydrochloric acid. The reaction time was 50min, and the polyacid nanocapsule-like molecules POM modified with dimethylamine borane were obtained by cooling and filtering;
[0043] Step S2: 3 g of dimethylamine borane-modified polyacid nanocapsule molecules POM and 9 g of Mn-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 150 ° C, the reaction time was 40 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 80 ° C for 12 h.
[0044] Step S3: adding 2gPOM@MOF, 7gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanosilica and 1gpolyvinylpyrrolidone K60 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 3gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanosilica and 1gpolyvinylpyrrolidone K60 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0045] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 100°C for 3 hours. The graphite felt high-temperature sintering process is as follows: the temperature is increased to 300°C at a heating rate of 6°C / min and kept warm for 3 hours to obtain a graphite felt with adjustable hardness and softness.
[0046] Embodiment 4: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0047] Step S1: 16gH7[P2Mo 17 VO 62] and 4g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g morpholine borane was added, and the pH value was adjusted to 1 with hydrochloric acid. The reaction time was 35min, and the polyacid nanocapsule molecules modified with morpholine borane were obtained by cooling and filtering;
[0048] Step S2: 2.4 g of morpholine borane-modified polyacid nanocapsule molecules POM and 12 g of Mn-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 160 ° C, the reaction time was 30 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 60 ° C for 18 h.
[0049] Step S3: adding 2gPOM@MOF, 8gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanosilica and 1gpolyvinylpyrrolidone K90 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 4gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanosilica and 1gpolyvinylpyrrolidone K90 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0050] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 110°C for 2 hours. The graphite felt high-temperature sintering process: the temperature is increased to 320°C at a heating rate of 8°C / min and kept warm for 2.5 hours to obtain graphite felt with adjustable hardness and softness.
[0051] Embodiment 5: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0052] Step S1: 18gH7[P2Mo 17 VO 62 ] and 4.5g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g morpholine borane was added, and the pH value was adjusted to 2 with hydrochloric acid. The reaction time was 60min, and the polyacid nanocapsule molecules modified with morpholine borane were obtained by cooling and filtering;
[0053] Step S2: 3 g of morpholine borane-modified polyacid nanocapsule molecules POM and 15 g of Mn-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added for hydrothermal reaction at a temperature of 180 ° C for 20 h. After cooling to room temperature, centrifugation was performed and vacuum drying was performed to obtain POM@MOF at a vacuum drying temperature of 70 ° C for 10 h.
[0054] Step S3: adding 2gPOM@MOF, 9gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanosilica and 1gpolyvinylpyrrolidone K150 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 4gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanosilica and 1gpolyvinylpyrrolidone K150 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0055] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 120°C for 2 hours. The graphite felt high-temperature sintering process: the temperature is increased to 350°C at a heating rate of 9°C / min and kept warm for 2 hours to obtain graphite felt with adjustable hardness and softness.
[0056] Embodiment 6: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0057] Step S1: 20gH7[P2Mo 17 VO 62 ] and 5g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g morpholine borane was added, and the pH value was adjusted to 1.5 with hydrochloric acid. The reaction time was 45min, and the polyacid nanocapsule molecules modified with morpholine borane were obtained by cooling and filtering;
[0058] Step S2: 1 g of morpholine borane-modified polyacid nanocapsule molecule POM and 3 g of Mn-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 200 ° C, the reaction time was 20 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 8 ° C and a time of 8 h.
[0059] Step S3: adding 2gPOM@MOF, 10g carbon nanotubes, 0.5g polyvinyl alcohol, 0.5g sodium dodecylbenzene sulfonate, 1g nano-alumina and 1g polyvinyl pyrrolidone K15 to 100g deionized water, dispersing them evenly, and obtaining modified A carbon slurry; adding 2gPOM@MOF, 5g carbon nanotubes, 0.5g polyvinyl alcohol, 0.5g sodium dodecylbenzene sulfonate, 1g nano-alumina and 1g polyvinyl pyrrolidone K15 to 100g deionized water, dispersing them evenly, and obtaining modified B carbon slurry;
[0060] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 80°C for 5 hours. The graphite felt high-temperature sintering process: the temperature is increased to 250°C at a heating rate of 8°C / min and kept warm for 4 hours to obtain graphite felt with adjustable hardness and softness.
[0061] Embodiment 7: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0062] Step S1: 20gH7[P2Mo 17 VO 62 ] and 5g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g morpholine borane was added, and the pH value was adjusted to 2.5 with hydrochloric acid. The reaction time was 60min, and the polyacid nanocapsule molecules modified with morpholine borane were obtained by cooling and filtering;
[0063] Step S2: 3 g of morpholine borane-modified polyacid nanocapsule molecules POM and 3 g of Mn-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 200 ° C, the reaction time was 20 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 80 ° C and a time of 8 h.
[0064] Step S3: adding 2gPOM@MOF, 8gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K90 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 4gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K90 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0065] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 120°C for 2 hours. The graphite felt high-temperature sintering process: the temperature is increased to 350°C at a heating rate of 10°C / min and kept warm for 2.5 hours to obtain graphite felt with adjustable hardness and softness.
[0066] Embodiment 8: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0067] Step S1: 10gH7[P2Mo 17 VO 62] and 2.5g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g 2-methylpyridine borane was added, and the pH value was adjusted to 2 with hydrochloric acid, the reaction time was 20min, and the polyacid nanocapsule molecules modified with 2-methylpyridine borane were obtained by cooling and filtering;
[0068] Step S2: 3g 2-methylpyridine borane modified polyacid nanocapsule molecule POM and 6g Ni-MOF were added to a reactor, 1000mL N-N dimethylformamide was added, the hydrothermal reaction temperature was 150°C, the reaction time was 60h, cooled to room temperature and centrifuged, vacuum dried to obtain POM@MOF, the vacuum drying temperature was 80°C, and the time was 12h;
[0069] Step S3: adding 2gPOM@MOF, 5gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K15 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 1gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K15 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0070] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 80°C for 5 hours. The graphite felt high-temperature sintering process: the temperature is increased to 250°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain graphite felt with adjustable hardness and softness.
[0071] Embodiment 9: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0072] Step S1: 15gH7[P2Mo 17 VO 62 ] and 3.75g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g 2-methylpyridine borane was added, and the pH value was adjusted to 1 with hydrochloric acid. The reaction time was 60min, and the polyacid nanocapsule molecules modified with 2-methylpyridine borane were obtained by cooling and filtering;
[0073] Step S2: 1 g of 2-methylpyridine borane-modified polyacid nanocapsule-like molecule POM and 4 g of Ni-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 200 ° C, the reaction time was 30 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 60 ° C for 24 h.
[0074] Step S3: adding 2gPOM@MOF, 7gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K15 to 100gdeionized water, and dispersing them uniformly to obtain modified A carbon slurry; adding 2gPOM@MOF, 1gcarbon nanotubes, 0.5gpolyvinyl alcohol, 0.5gsodium dodecylbenzenesulfonate, 1gnanoalumina and 1gpolyvinylpyrrolidone K15 to 100gdeionized water, and dispersing them uniformly to obtain modified B carbon slurry;
[0075] Step S4: The graphite felt is impregnated with modified carbon slurry A to a thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified carbon slurry B to a thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 80°C for 4 hours. The graphite felt high-temperature sintering process: the temperature is increased to 350°C at a heating rate of 5°C / min and kept warm for 3 hours to obtain graphite felt with adjustable hardness and softness.
[0076] Embodiment 10: A method for preparing a soft and hard adjustable ink felt for a vanadium battery, comprising the following steps:
[0077] Step S1: 20gH7[P2Mo 17 VO 62 ] and 5g sodium bisulfate were dissolved in 1000g 80℃ deionized water, and then 1g 2-methylpyridine borane was added, and the pH value was adjusted to 3 with hydrochloric acid, and the reaction time was 20min. The polyacid nanocapsule molecules modified with 2-methylpyridine borane were obtained by cooling and filtering;
[0078] Step S2: 1 g of 2-methylpyridine borane-modified polyacid nanocapsule-like molecule POM and 4 g of Ni-MOF were added to a reactor, and 1000 mL of N-N-dimethylformamide was added. The hydrothermal reaction temperature was 200 ° C, the reaction time was 30 h, and the reaction was centrifuged after cooling to room temperature. The POM@MOF was obtained by vacuum drying at a vacuum drying temperature of 60 ° C for 24 h.
[0079] Step S3: Add 2gPOM@MOF, 10gCNTs, 0.5gPVA, 0.5gSodium dodecylbenzenesulfonate, 1gNanosilica and 1gPVP K15 into 100gdeionized water and disperse them evenly to obtain modified A carbon slurry; add 2gPOM@MOF, 1gCNTs, 0.5gPVA, 0.5gSodium dodecylbenzenesulfonate, 1gNanosilica and 1gPVP K15 into 100gdeionized water and disperse them evenly to obtain modified A carbon slurry; Ketone K15 is added to 100g of deionized water and dispersed evenly to obtain modified B carbon slurry; step S4: the graphite felt is impregnated with modified A carbon slurry with an impregnation thickness of 1 / 2 of the thickness of the graphite felt, and the graphite felt is impregnated with modified B carbon slurry with an impregnation thickness of 1 / 2 of the thickness of the graphite felt. The graphite felt is dried at 80°C for 5h. The graphite felt is sintered at a high temperature at a heating rate of 10°C / min to 250°C and kept warm for 4h to obtain a graphite felt with adjustable hardness and softness.
[0080] Comparative Example 1: The preparation process of this comparative example is different from that of Example 1 only in that POM@MOF is not added to the carbon slurry.
[0081] Comparative Example 2: The preparation process of this comparative example is different from that of Example 1 only in that only MOF material is added to the carbon slurry.
[0082] Comparative Example 3: The preparation process of this comparative example is different from that of Example 1 only in that the carbon slurry and carbon nanotube concentrations impregnated on both sides of the graphite felt are the same.
[0083] Comparative Example 4: This comparative example is a blank control group, that is, untreated blank graphite felt is used.
[0084] The graphite felts prepared in Examples 1-10 and Comparative Examples 1-4 were cut into a size of 3 cm*3 cm, copper plates were placed at both ends, and a low resistance tester was used to clamp the copper plates at both ends to test the resistance value at 20% deformation. Contact resistance = resistance value - material body resistance.
[0085] The graphite felts prepared in the embodiment and the comparative example were assembled into battery stacks and charged and discharged under the same test conditions, and the battery coulombic efficiency, voltage efficiency, energy efficiency, capacity retention rate after 100 cycles and electrolyte utilization rate were recorded, where electrolyte utilization rate = actual discharge capacity / theoretical discharge capacity. The test results are shown in Table 1:
[0086] Table 1: Battery performance test table of battery stacks assembled using the embodiment and the comparative example
[0087]
[0088] It can be seen from the comparison between Example 1 and Comparative Example 1 that, since POM@MOF has rich topological structures and high active sites and a large specific surface area, it can improve the conductivity of graphite felt and its electrochemical performance. However, POM@MOF is not added in Comparative Example 1, so the voltage efficiency is slightly reduced. By comparing Example 1 with Comparative Example 2, it can be seen that the use of organic boron to treat Dawson-type mixed polyacid H7[P2Mo 17 VO 62 ] is covalently modified and loaded into the MOF pores, combining the porosity of the MOF material with the high reactivity of the polyacid, which can increase the specific surface area and surface active points of the polyacid, thereby improving the reactivity of the graphite felt. In Comparative Example 2, only MOF material is added, and no polyacid that can provide surface active points is added, so the performance of the graphite felt is slightly worse; by comparing Example 1 with Comparative Example 3, it can be seen that the concentration of carbon nanotubes in the carbon slurry impregnated with the graphite felt in Comparative Example 3 is the same, resulting in both sides of the graphite felt after sintering being harder, causing physical damage to the ion membrane during the assembly of the stack, and reducing the coulombic efficiency.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing graphite felt with adjustable hardness for vanadium batteries, characterized in that: The following steps are involved: S1. Use organic boron to treat H7[P2Mo 17 VO 62 ] is covalently modified to obtain organic boron-modified polyacid nano-capsule molecules; the covalent modification method is: H7[P2Mo 17 VO 62 ] and sodium bisulfate are dissolved in 80°C deionized water, and then organic boron is added, and the pH value is adjusted to 1-3 with hydrochloric acid, the reaction time is 20-60 minutes, and the polyacid nanocapsule molecules modified with organic boron are obtained by cooling and filtering; S2. Loading the organoboron-modified polyacid nanocapsule-like molecules into the pores of the metal organic framework material through a hydrothermal reaction to obtain POM@MOF; the hydrothermal reaction method is: uniformly dispersing the organoboron-modified polyacid nanocapsule-like molecules, the metal organic framework material and NN dimethylformamide to obtain a mixed solution, adding the mixed solution to a reactor, reacting at 120-200° C. for 20-60 hours, cooling to room temperature and centrifuging, and vacuum drying the precipitate at 60-80° C. for 8-24 hours to obtain POM@MOF; S3, adding POM@MOF, carbon nanotubes, dispersant, surfactant, stabilizer and high-temperature crosslinking agent into deionized water, dispersing them evenly, and adjusting the proportion of carbon nanotubes to obtain modified A carbon slurry and modified B carbon slurry; S4. Immerse one side of the graphite felt in modified carbon slurry A and the other side in modified carbon slurry B. After immersion, dry it in an oven and then perform high-temperature sintering to obtain graphite felt with adjustable hardness and softness.
2. The method for preparing a graphite felt with adjustable hardness for vanadium battery according to claim 1, characterized in that: In step S1, the organic boron is selected from one of dimethylamine borane, morpholine borane and 2-methylpyridine borane.
3. The method for preparing a graphite felt with adjustable hardness for vanadium battery according to claim 1, characterized in that: In step S1, H7[P2Mo 17 VO 62 ], the mass ratio of organic boron and deionized water is (10~20): 1:1000, H7[P2Mo 17 VO 62 ] and sodium bisulfate is 4:
1.
4. The method for preparing a graphite felt with adjustable hardness for vanadium battery according to claim 1, characterized in that: The metal organic framework material is a copper-based metal organic framework, a manganese-based metal organic framework, and a nickel-based metal organic framework; the concentrations of the polyacid nanocapsule-like molecules modified by organic boron and the metal organic framework material in the mixed solution are 1-3 g / L and 3-15 g / L, respectively, and the concentration ratio of the polyacid nanocapsule-like molecules modified by organic boron to the metal organic framework material is 1:1-1:
5.
5. The method for preparing a graphite felt with adjustable hardness for vanadium battery according to claim 1, characterized in that: In step S3, the dispersant is polyvinyl alcohol, the surfactant is sodium dodecylbenzene sulfonate, the stabilizer is one of nano-alumina and nano-silicon dioxide, and the high-temperature cross-linking agent is one of polyvinyl pyrrolidone K15, polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K60, polyvinyl pyrrolidone K90, and polyvinyl pyrrolidone K150.
6. The method for preparing a graphite felt with adjustable hardness for vanadium battery according to claim 1, characterized in that: In the step S3, the mass ratio of the components of the modified A slurry is 2: (5-10): 0.5: 0.5: 1: 1: 100 for POM@MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water; the mass ratio of the components of the modified B slurry is 2: (1-5): 0.5: 0.5: 1: 1: 100 for POM@MOF: carbon nanotubes: dispersant: surfactant: stabilizer: high temperature crosslinking agent: deionized water.
7. The method for preparing a graphite felt with adjustable hardness for vanadium battery according to claim 1, characterized in that: In the step S4, the impregnation method is: the graphite felt is impregnated with modified carbon slurry A with a thickness of 1 / 2 of the graphite felt thickness, and the impregnation with modified carbon slurry B with a thickness of 1 / 2 of the graphite felt thickness; the drying temperature is 80-120°C, and the drying time is 2-5h; the high-temperature sintering process of the graphite felt is: heating to 250-350°C at a heating rate of 5-10°C / min, and keeping warm for 2-4h.
8. A graphite felt with adjustable hardness for vanadium battery, characterized by: The adjustable hardness graphite felt is prepared by the method for preparing adjustable hardness graphite felt for vanadium battery as described in any one of claims 1 to 7; in the vanadium battery stack, the harder side of the graphite felt contacts the plate, and the softer side of the graphite felt contacts the diaphragm.
Citation Information
Patent Citations
Design synthesis of covalent organic framework material of post-modified carborane and application of covalent organic framework material in lithium-sulfur battery diaphragm
CN114709557A
Porous carbon structure, manufacturing method therefor, and lithium secondary battery comprising same
WO2022164213A1